DAMPAK GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KINERJA KARYAWAN: SEBUAH STUDI EMPIRIS - Karomah, Siti; Almaidah, Siti (JURNAL ILMIAH EDUNOMIKA, 2024)
Human Resources (HR) serves as a crucial foundation for the company in achieving its objectives. The elements contained in HR include sources of knowledge, skills, and abilities. Companies find themselves in a situation where enhancing employee performance is essential, as strong employee performance can significantly contribute to overall company success. This research investigates how transformational leadership style, the work environment, and organizational citizenship behavior influence the performance of sewing workers at PT Eco Smart Garment Indonesia. This study involved 83 respondents and was drawn using purposive sampling with restrictions including permanent employees and more than one year of service. Data were collected using survey, interview, and documentation methods. Measurement of statements used a Likert scale with a weight of 1-5. Data analysis techniques are carried out through descriptive testing, data quality tests, classical assumption tests, multiple linear regression analysis, model accuracy tests, determination coefficient tests, and hypothesis testing. The important findings of the study are transformational leadership style, work environment, organizational citizenship behaviour affect employee performance positively and significantly. Meanwhile, the dominant influence on employee performance is transformational leadership style.